IMPLEMENTATION OF THE SLOVENIAN ACT ON THE TREATMENT OF CHILDREN AND ADOLESCENTS WITH EMOTIONAL AND BEHAVIOURAL PROBLEMS OR DISORDERS IN EDUCATION - Vukovič, Matej; Krajnčan, Mitja; Vrhunc Pfeifer, Katja (International Journal of Child, Youth and Family Studies, 2025)
In 2020, Slovenia implemented the Act on the Treatment of Children and Adolescents With Emotional and Behavioural Problems or Disorders in Education. Using a mixed-methods approach, we investigated how professionals in expert centres and social work centres, youth judges, and paedopsychiatrists, as key stakeholders responsible and competent for the professional and lawful treatment of such youth, seek and implement the most appropriate forms of assistance for them, and how they assess the implementation of the Act and the cooperation amongst them. Data were collected through four tailored questionnaires, as well as focus groups and semi-structured interviews. The research is part of a larger Slovenian study entitled Phenomenological and aetiological analysis of emotional and behavioural problems and disorders and the development of didactic approaches for specific subtypes of problems and disorders, not yet published. Based on the opinions of these experts from various fields, we identified shortcomings in the system of support, including what should be eliminated or changed, and what new forms of support and cooperation among stakeholders would be reasonable and necessary to introduce. The results of the survey are also important for understanding the competences, responsibilities, and cooperation among social work centres, expert centres, paedopsychiatrists, and youth judges.